Results of Outreach Referral Program After Failed In-School Eye Examinations - Kayla Tucker; Sergul A. Erzurum; Tahir Kuraan (Ohio Journal of Public Health, 2024)
Background: The absence of childhood vision care has detrimental consequences on development and learning. The Vision Health Initiative Committee (VHI) was established by the Centers for Disease Control and Prevention (CDC) to mandate school vision screenings. Improved detection does not translate into vision care. Poor compliance for follow-up remains an issue. This study evaluates the effectiveness of an outreach referral program specializing in assisting families with recommended follow-up care for children following in-school eye examinations. Methods: A mobile vision van provided in-school eye examinations and dispensed eyeglasses to at-risk children. Referrals for in-office evaluation were generated for children with more serious medical conditions. Each family was contacted via phone call and/or text message to assist in scheduling their child with an eye examination. Results of the communications were tabulated and analyzed. Results: The mobile vision van program completed 13 260 vision screenings and provided 2185 eye examinations to children in Northeast Ohio. Out of the 2185 examinations, 238 (11%) students required further evaluation. Of those 238, the families of 165 (70%) were successfully contacted; 75 (45%) families had scheduled their own follow-up appointment, 77 (47%) families needed assistance to schedule an examination, and 13 (8%) families were not interested in further assistance. Of the 77 receiving assistance with scheduling, 54 (70%) families kept the scheduled appointment and received care at no cost. Conclusion: This study further substantiates the health disparity in eye care. It demonstrates the importance of in-school vision examinations and the value of an outreach referral program which includes education and assistance with scheduling appointments.
Keywords: Pediatrics; Vision care; Eyeglasses; Referral; Retrospective review